IMPLEMENTASI MODEL PEMBELAJARAN SENTRA DALAM MENINGKATKAN KEMANDIRIAN ANAK USIA DINI DI PAUD DWP KANWIL KEMENTRIAN AGAMA PROVINSI SULAWESI TENGAH - Al-Aydrus, Nurlaila (Pusat Studi Gender dan Anak, IAIN Palu, 2024)
Independence is one of the characters that needs to be possessed and instilled in children from an early age. The purpose of this study is to describe the efforts made in instilling children's independence through learning in the block center at PAUD DWP Regional Office of the Ministry of Religious Affairs of the Province, Central Sulawesi, The research method used is qualitative with a descriptive qualitative approach. Data collection is carried out by interviews, observations and documentation. The data sources in this study are school principals, teachers and children of Group A4 at the beam center at the PAUD DWP Regional Office of the Ministry of Religion of Central Sulawesi Province, Data analysis was carried out using the Interactive Model data analysis technique from Miles and Huberman which includes data reduction, data presentation and data verification. The data is presented in the form of narratives and images. The results of the study show that the cultivation of children's independence through learning at the PAUD DWP Block Center of the Regional Office of the Ministry of Religion of Central Sulawesi Province is carried out by applying the rules of the game consistently at the time of footing before playing, which includes the following rules: 1. take and return the block in its place; 2. Take care of the beam; 3. the block is shared with friends; and 4. Take a block to taste.